Role of the Ventral Striatal Pathways in Reinforcement Learning: Chemogenetic Modulation During the Incubation of Craving - Silva, Phillip Rey (My University, 2024)
Cocaine addiction is a major public health problem with high rates of relapse. The incubation of cocaine craving, characterized by an increase in cue-induced cocaine seeking behavior after abstinence, is thought to play a key role in relapse. Previous research has suggested that the ventral striatum, particularly the nucleus accumbens (NAc), is critical for the expression of cocaine-seeking behavior. Furthermore, the serotonin 5-HT1B receptor has been implicated in the regulation of cocaine-seeking behavior. However, the specific role of 5-HT1B receptors in the NAc following the incubation of cocaine craving remains unclear. In this study, we chose to investigate the role of 5-HT1B receptors in the ventral striatal pathways following the incubation of cocaine craving. We used long and short access self-administration behavioral models and cre-dependent viral expression of RiboTag and hM4Di in D1 and A2a transgenic rats to assess differences in either the direct or indirect pathways in the NAc. After a period of abstinence, we will assess the incubation of cocaine craving by measuring cue-induced cocaine seeking behavior. To examine the role of 5-HT1B receptors in the NAc, we will use RiboTag immunoprecipitation selectively isolate mRNA from D1 and A2a receptor-expressing neurons in the NAc. We will then use qPCR to measure mRNA levels of 5-HT1B receptors in these neurons following the incubation of cocaine craving. We hypothesize that the incubation of cocaine craving will be associated with increased cue-induced cocaine seeking behavior and changes in 5-HT1B receptor expression in D1 and A2a receptor-expressing neurons in the NAc. Our findings further implicate 5-HT1B receptors in the processing of stress, reward processing, and relapse; additionally, this study suggests unique roles of the ventral striatal pathways following prolonged abstinence. This information could have implications for the development of new treatments for cocaine addiction.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: dopamine receptors; drug addiction; incubation of craving; lateral habenula; rodent behavior; ventral striatum; Neurosciences; Psychology; Pharmacology; Behavioral neuroscience